Bioactivity of biosilica obtained from North Atlantic deep-sea sponges - Dudik, Olesia (2021)
Demosponges are a well-known source of a plethora of bioactive compounds. In particular, they are able to form a skeleton by direct deposition of silica in a process catalysed by silicatein. Herein, we isolated biosilicas from five different Atlantic deep-sea sponges Geodia atlantica (GA), Geodia barretti (GB), Stelletta normani (SN), Axinella infundibuliformis (AI) and Phakellia ventilabrum (PV) to explore the bioactivity and osteogenic capacity of its silica-based materials. We chemically characterized the isolated biosilicas and evaluated them for their bioactivity to deposit Ca and P on their surface (by immersion in simulated body fluid, SBF). GB-, SN-, AI- and PV-based biosilicas did not generate a stable calcium phosphate (CaP) layer over time in the presence of SBF, however, the GA-derived one was able to form a CaP surface layer (at a Ca/P ratio of ~1.7, similar to the one observed for hydroxyapatite), that was stable during the 28 days of testing. In addition, no cytotoxicity towards L929 and SaOs2 cells was observed for the GA-based biosilica up to a concentration of 10 mg/mL. Overall, the GA-based biosilica presents the characteristics to be used in the development of biomaterials for bone tissue engineering (BTE).